Subclinical neurodegeneration in multiple sclerosis and neuromyelitis optica spectrum disorder revealed by optical coherence tomography. (September 2020) - Pisa, Marco; Ratti, Francesco; Vabanesi, Marco; Radaelli, Marta; Guerrieri, Simone; Moiola, Lucia; Martinelli, Vittorio; Comi, Giancarlo; Leocani, Letizia
Background: Neuroretinal atrophy is associated with whole-brain atrophy and disease activity in multiple sclerosis (MS). Recent findings support that subclinical visual pathway involvement might also occur in neuromyelitis optica spectrum disorders (NMOSDs). Objective: The objective of this study is to assess retinal thinning in MS and NMOSD and its association with disease activity. Methods: In total, 27 NMOSD and 54 propensity-score-matched MS patients underwent optical coherence tomography, visual acuity, and visual-evoked potentials at 2.4 years apart, in addition to routine clinical and magnetic resonance imaging (MRI) assessment. We excluded eyes with acute optic neuritis. Results: In NMOSD, we detected peripapillary retinal nerve fiber layer (pRNFL) thinning in patients with disease activity during follow-up (−0.494 µm/year), but not in stable patients (−0.012 µm/year). Macular ganglion cell-inner plexiform layer (GCIPL) thinning occurred instead in all patients (−0.279 µm/year). Relapsing–remitting multiple sclerosis (RRMS) meeting NEDA-3 criteria had no pRNFL or GCIPL thinning during follow-up. Active-disease RRMS and progressive MS, both active and stable, displayed pRNFL (−0.724, −0.586, −0.556 µm/year, respectively) and GCIPL loss. Conclusion: In MS, neuroretinal atrophy was associated with disease activity but occurred in progressive MS even when achieving NEDA-3 criteria. In NMOSD, pRNFL thinning was associated with non-ocular relapses due to a spreading of inflammatory activity. GCIPL thinning was found in all patients, supporting a primary retinal pathology targeting AQP4-rich structures.